BiPOLES is an optogenetic tool developed for bidirectional dual-color control of neurons - Vierock, Johannes; Rodriguez-Rozada, Silvia; Dieter, Alexander; Pieper, Florian; Sims, Ruth; Tenedini, Federico; Bergs, Amelie C. F.; Bendifallah, Imane; Zhou, Fangmin; Zeitzschel, Nadja; Ahlbeck, Joachim; Augustin, Sandra; et al. (Nature Communications, 2021)
Optogenetic manipulation of neuronal activity through excitatory and inhibitory opsins has become an indispensable experimental strategy in neuroscience research. For many applications bidirectional control of neuronal activity allowing both excitation and inhibition of the same neurons in a single experiment is desired. This requires low spectral overlap between the excitatory and inhibitory opsin, matched photocurrent amplitudes and a fixed expression ratio. Moreover, independent activation of two distinct neuronal populations with different optogenetic actuators is still challenging due to blue-light sensitivity of all opsins. Here we report BiPOLES, an optogenetic tool for potent neuronal excitation and inhibition with light of two different wavelengths. BiPOLES enables sensitive, reliable dual-color neuronal spiking and silencing with single- or two-photon excitation, optical tuning of the membrane voltage, and independent optogenetic control of two neuronal populations using a second, blue-light sensitive opsin. The utility of BiPOLES is demonstrated in worms, flies, mice and ferrets.
CRIS-Team Scopus Importer:2021-11-16